Radio cognitivo embarcado para internet das coisas - Mazzer, Daniel (2016)
Studies from researching companies estimates an unprecedented growth in the amount of electronic devices communicating wirelessly. With tens of billions of devices sharing the radio frequency spectrum the efficient use of the spectrum becomes an important concern. Cognitive radio has been proposed as a solution for a more efficient radio frequency spectrum allocation where primary user channels are allocated by unlicensed secondary users. This work was carried out the design and implementation of CogRIoT, a low-cost embedded cognitive radio platform applied to Internet of Things. The platform was designed to operate in a distributed architecture and may be applied over licensed or unlicensed channels. Also, this work associates spectral sensing techniques, embedded platforms, future Internet and software defined radio architecture. Performance evaluation were conducted making use of Internet of Things devices, showing the benefit of the combination of two major topics in telecommunications.